OTORITAS LEMBAGA ADAT DALAM MENEGAKKAN SYARI’AT ISLAM DI ACEH - Burhanuddin Banta Cut (Jurnal Tahqiqa : Jurnal Ilmiah Pemikiran Hukum Islam, 2015)
Implementation of Shari'a in Aceh is inseparable from the role oftraditional institutions that exist at various levels of the community. Suchinstitutions as long as it has a fairly broad authority for the implementation of thelaws of the various problems faced by the people of Aceh. The laws in forcebefore the implementation of Islamic Shariah approved in many ways refers to thelaw that formed in the community since the time that has past. The laws areimplemented by institutions that are recognized by the community as a sourcereference implementation of the law in various problems faced by localcommunities.